Efficient Method of Transporting Coconut (Cocos nucifera L.) Zygotic Embryos for Cryopreservation of Plumules by Encapsulation/Dehydration - Bandupriya, H. D. D.; Fernando, S. C.; Verdeil, Jean-Luc; Malaurie, Bernard (International Coconut Community, 2014)
Coconut is both socially and economically important crop in tropical and subtropical countries, thus the conservation of existing diversity of its germplasm is vital to maintain biodiversity, sustain crop production and utilisation of germplasm for crop improvement strategies. The recalcitrant storage behavior and large size of the coconut seed make it impossible to use as a germplasm storage material. Cryopreservation is an ideal means of long-term storage of germplasm which offers long-term storage capability with minimal storage space and maintenance requirements. The coconut embryo has been now adapted by various researchers for the purpose of germplasm exchange and it is now being routinely applied in germplasm collection and exchange activities with sufficient germination rates. The aim of the present study was to determine the effect of different coconut embryo transport/ storage methods [as solid endosperm plugs under cold temperature, embryos cultured in Solidified Agar Medium (SAM) or KCl solution under room temperature] on cryopreservation of plumules using encapsulation/dehydration method. The results revealed that plumules excised from embryos transported/ stored in SAM and pretreated with 1.0M sucrose could be cryopreserved with 71.8% survival and 56% recovery rates. The survival and recovery could be further increased up to 77.5% and 65% respectively by supplementation of 1.0M sucrose with 20 µM ABA.